Digitalization in the manufacturing sector : skills in transition - Kleinsmith, Niela, (SAGE Business Cases., 2018)
With the introduction of new machining technologies in his workplace, 50-year-old machine operator Paul Sandberg is confronted with the realisation that the skills and experience that he's gained on the job over the course of his career are now mostly worthless. He has learned new skills in operating the new CNC machines, but he has lost some job autonomy and responsibility. Additionally, his hierarchical superior, on whom he is now dependent for the progress of his work, is more than 20 years his junior, and his new operator colleagues have significantly less skills training than he has. Like the machines he used to manually operate, Paul now feels somewhat obsolete and is having a hard time relating to his new colleagues and working environment.